Analisis Pengaruh Proses Pengeringan Nata De Coco Terhadap Pertumbuhan Jamur Pada Bioselulosa Nata De Coco - Hidayat, Ade Nurul; Irwati, Dwi (DPPM UNIVERSITAS PELITA BANGSA, 2021)
Indonesia is the number two coconut producing country in the world. Indonesia's coconut soil productivity is still low compared to Sri Lanka and India. Demand for coconut -based products continues to increase, both for export and for the domestic market. The main product of nata de coco apart from being an export material, can also have other potential that can be utilized by diversifying nata de coco derivative products. The use of biocellulose contained in nata de coco into bio sheet, bio cellulose mask, bio fiber pulp and bio fiber powder is an opportunity to diversify products and increase exports. The purpose of this study was to determine the effect of nata de coco drying process on fungal growth in nata de coco biocellulose. The tools and materials used were nata de coco (sheet), vacuum oven, manual press, cloth material, analytical balance with precision (0.01g) and SEM test equipment (microscopic electron scanning) at PT. CMM. In the method of analysis, this research uses quantitative and qualitative analysis methods, then to see the development of fungi from different types of drying having different % water content so that we can know how long the best drying time for drying nata de coco so. That it is not easily attacked by fungi. In the process of making nata de coco that has been collected from sellers/distributors of nata de coco obtained from nata de coco farmers in Cianjur. Dried in an oven at 950C for 1-5 hours to become dry biocellulose fibers. In the nata de coco water content test, the water content was 93.48% and from the water content characteristic test results, the best water content and biocellulose were obtained at the composition of 91.32% water content and 8.68% biocellulose on heating for 5 hours.